Religion, Life Expectancy, and Disability-Free Life Expectancy Among Older Women and Men in the United States. (24th August 2018) - Ofstedal, Mary Beth; Chiu, Chi-Tsun; Jagger, Carol; Saito, Yasuhiko; Zimmer, Zachary
Abstract: Objectives: Existing literature shows religion is associated with health and survival separately. We extend this literature by considering health and survival together using a multistate life table approach to estimate total, disability-free, and disabled life expectancy (LE), separately for women and men, for 2 disability measures, and by 2 indicators of religion. Method: Data come from the Health and Retirement Study (1998–2014 waves). Predictors include importance of religion and attendance at religious services. The disability measures are defined by ADLs and IADLs. Models control for sociodemographic and health covariates. Results: Attendance at religious services shows a strong and consistent association with life and health expectancy. Men and women who attend services at least once a week (compared with those who attend less frequently or never) have between 1.1 and 5.1 years longer total LE and between 1.0 and 4.3 years longer ADL disability-free LE. Findings for IADL disability are similar. Importance of religion is related to total and disabled LE (both ADL and IADL), but the differentials are smaller and less consistent. Controlling for sociodemographic and health factors does not explain these associations. Discussion: By estimating total, disability-free, and disabled LE, we are able to quantify the advantage of religion for health. Results are consistent with previous studies that have focused on health and mortality separately.